ผลของซีพีพี-เอซีพีเพสต์ต่อความแข็งของเคลือบฟันที่สัมผัสกับคลอรีน : การศึกษาในห้องปฏิบัติการ - ธาริณี พนมเริงศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objective The purpose of this study was to assess the effect of casein phosphopeptide-amorphous calciumphosphate paste (CPP-ACP paste) on intact enamel exposed to chlorinated water. Materials and methods Twelve human premolars extracted for orthodontic reason were prepared for hardness measurement using nanoindentation system. The specimens were randomly divided into two groups. The experimented group was applied with CPP-ACP paste on intact enamel surface for three minutes and immersed in artificial saliva for 30 minutes while the controlled group was left unapplied. Hardness in GPa was measured before and after being exposed to chlorinated water (pH 5.3) for 2 hours and artificial saliva for 8 hours. The data were analyzed by Wilcoxon signed rank test (=0.05). Results The result showed that the hardness of the intact enamel before and after exposed to chlorinated water (pH 5.3) for 2 hours and artificial saliva for 8 hours was insignificantly changed in both of the controlled group (4.34±0.92 and 4.38±0.72 GPa) and experimented group (4.91±0.32 and 5.05±1.29 GPa). Conclusion We concluded that CPP-ACP paste did not have any effect on enamel hardness exposed to chlorinated water (pH 5.3) for 2 hours and artificial saliva for 8 hours in vitro.